Compression of the left mainstem bronchus by patent ductus arteriosus in neonates under consideration for ductal stenting. Issue 6 (20th January 2020) - Smith, Christopher L.; Saul, David; Goldfarb, Samuel B.; Biko, David M.; O'Byrne, Michael L.
Abstract: Stent angioplasty of patent ductus arteriosus has been shown to be a viable alternative to operative shunt placement in cyanotic neonates. With broader implementation of this strategy, novel complications are bound to arise. We present a series of cases evaluated for ductal stent angioplasty in which a dilated and torturous ductus arteriosus compressed the left mainstem bronchus. After reviewing our recent experience with ductal stenting and isolated Blalock‐Taussig shunts, our best estimate of the incidence of bronchial compression by the dilated ductus is 4.6% (3/64, 95% confidence interval 1.0–12.9%). Awareness of the airway and other nonvascular contents of the thorax is an important consideration prior to ductal stenting.